Karate, capoeira and MMA: a phenomenological approach to the process of starting a fight (Revista de Artes Marciales Asiáticas, 2018)
In sports studies, the body of research focussing on combat sports has developed, but so far few studies regarding the experience of starting a fight. In order to comprehend the process of starting a fight, this study aims to investigate and describe it through both a comparative and phenomenological approach of Brazilian karate, capoeira and mixed martial arts (MMA) practitioners (n = 11, 7, 11, respectively). Semi-structured interviews were conducted and in the analysis we used a phenomenological perspective. Most of the karatekas described the distance adjustment and bowing to their opponent as the beginning of the combat. Capoeiristas highlighted the sound of music and the roda, referring to the way they organize themselves to start fighting. MMA athletes commonly described the beginning of the fight as when they start the camp, from the weigh-in or the octagon entrance. Using the phenomenology of Merleau-Ponty, the process of beginning a fight can be understood as a relationship between a bodily consciousness and the world. The findings in this paper concur with the phenomenological understanding, according to which actions are not seen as randomly executed: instead they are pre-reflexively and corporeally understood, as well as situated within a specific context; this is illustrated in the manner a fight within each modality seems to begin somewhat differently, according to the specific modality in question. These results help us comprehend the beginning of the fight in which body and world are constantly intertwined. Future directions include comprehension of the fighting experience as a whole, understanding the perception and movement of these fighters through the entire combat, and enhancing phenomenological studies regarding bodily experiences.